Surface-defect-engineered photocatalyst for nitrogen fixation into value-added chemical feedstocks. Issue 18 (19th August 2020) - Chen, Xue; Li, Jing-Yu; Tang, Zi-Rong; Xu, Yi-Jun
Abstract : Surface-defect-engineered photocatalyst for nitrogen fixation. Abstract : Efficient dinitrogen (N2 ) utilization using nitrogen-containing compounds such as ammonia (NH3 ) and nitrates, which are essential materials for modern fertilizers, medicines, etc., is important to the development of human society. However, the industrial synthesis of NH3 and nitrates requires high temperatures and pressures along with massive energy consumption. In this context, photocatalytic N2 fixation is regarded as an alternative promising strategy for the synthesis of nitrogen-containing compounds under ambient conditions. In this minireview, fundamental photocatalytic N2 fixation mechanisms, including N2 photoreduction to NH3 and photooxidation to nitrates, are initially elaborated. Then, we focus on the effects of surface defect engineering ( e.g., surface vacancies and heteroatom dopants) over semiconductor-based photocatalysts for efficient N2 fixation. Finally, we cast a personal perspective on the possible future challenges faced by defect-containing photocatalysts for N2 fixation. We hope that this minireview can shed light on the further development of rational designs of defect-containing photocatalysts toward efficient N2 fixation into diverse value-added chemical feedstocks.